PENGARUH TINGKAT PENDAPATAN, RELIGIUSITAS, AKUNTABILITAS DAN KUALITAS PELAYANAN TERHADAP MINAT MUZAKKI MEMBAYAR ZAKAT DI BAITUL MAL KOTA BANDA ACEH - Salmawati, Salmawati; Fitri, Meutia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study attempts to examie the imfluance factors that the determine the muzakki intention to pay zakat in zakat institution. The factors are income, religiosity, accountability and service quality of muzakki intention to pay zakat in Baitul Mal, Banda Aceh. This research type used in this study is Quantitave, that use primary data. The collecting data through quisionaire directly to research object. Each variable is the point to arrange the question items are measured by likert scale. The Sample of this research is 99 muzakki that pay zakat. Data processing was done by using multiple regression analysis and are processed by IBM Statistical Package for Sosial Science (SPSS) 21th version. The result of the research indicated that 44,8% The dependent variable for which is Intention on paying zakat can be explained by four of independent variables. Simultaneously shows that variables are income, religiusity, accountability and quality service are influance on muzakki intention to pay zakat in baitul mal, Banda Aceh.